PENGARUH VARIASI LUAS PERMUKAAN PLAT ELEKTRODA DAN KONSENTRASI LARUTAN ELEKTROLIT KOH TERHADAP DEBIT GAS HASIL ELEKTROLISIS AIR - Susanto, Agustinus; Rubiono, Gatut; Bunawi, Bunawi (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2016)
This research is aimed to get the effect of electrode surface area and electrolyteconcentration due to gas volume flow rate of water electrolysis. The surface area is varied as19.264 mm2, 38.528 mm2 and 57.792 mm2. The KOH electrolyte concentration is varied as 5 gram,10 gram, 15 gram, 20 gram, and 25 gram in a litre aquades. The experiment is conduct in an electrolyzer. HHO gas is flowed pass trough an orifice for volume flow rate measurement. The research shows that the increase surface area and electrolyte concentration tend to increase gasvolume flow rate. The maximum gas volume flow rate happened at 57792 mm2 surface area and25 gram KOH electrolyte concentration which is 0,00123 m3/det. The minimum gas volume flow rate happened at 19264 mm2 surface area and 5 gram KOH electrolyte concentration 0,00045 m3/det.